2023
DOI: 10.1021/acsomega.2c07492
|View full text |Cite
|
Sign up to set email alerts
|

Highly NH3 Sensitive and Selective Ti3C2O2-Based Gas Sensors: A Density Functional Theory-NEGF Study

Abstract: Ammonia (NH 3 ) detection at the early stage is an important precaution for human health and agricultural production. However, conventional sensing materials are difficult to achieve all the targeted operational performances such as low power consumption and high selectivity. MXenes are a type of graphene-like emergent material equipped with abundant surface sites benefiting gas-sensing applications. In the work, we discuss the sensing performance of Ti 3 C 2 O 2 to anticipate harmful and polluting NH 3 gases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It has proven to be especially useful in the study of molecular electrical structures. All the computational analyses have been performed using the DFT based Synopsys Quantum ATK software version 11.8 (Virtual Nano style).Generalized gradient approximation (GGA) with PBE (Perdew-Burke-Ernezherof) [8] type exchange-correlation function has been used to computed the structural and electronic properties of the Dimeric Pyrrole, Dimeric 3methylfuran and their copolymer. For the core and valence electronic states, double zeta polarised basis (DZP) [9] sets are used.…”
Section: Computational Methodologymentioning
confidence: 99%
“…It has proven to be especially useful in the study of molecular electrical structures. All the computational analyses have been performed using the DFT based Synopsys Quantum ATK software version 11.8 (Virtual Nano style).Generalized gradient approximation (GGA) with PBE (Perdew-Burke-Ernezherof) [8] type exchange-correlation function has been used to computed the structural and electronic properties of the Dimeric Pyrrole, Dimeric 3methylfuran and their copolymer. For the core and valence electronic states, double zeta polarised basis (DZP) [9] sets are used.…”
Section: Computational Methodologymentioning
confidence: 99%
“…This interaction induces the altering of the electronic structure of the system, leading to an observable electrical response. 69,70 The charge transfer processes are essential in influencing this mechanism, allowing for the detection and measurement of the target gas. 11,71 In this work, the charge transfer was obtained from Bader charge 72,73 calculations, which facilitate the comparison with previous studies in Section 3.5.…”
Section: Dft Screeningmentioning
confidence: 99%
“…Ideally, this necessitates the calculation of transport properties to obtain the relevant s value. Unfortunately, conducting such investigations and analyses of transport properties in materials requires extravagant computational power 69,74,75 and exceeds the scope of our capabilities and screening objective. Accordingly, the community has begun to employ a simpler property to semiquantitatively gauge the material's sensitivity in the screening process.…”
Section: Dft Screeningmentioning
confidence: 99%
“…Consequently, different functional groups show different values of adsorption energies of NH 3 molecules on Ti 3 C 2 surfaces, and this could be notified in a sequence as Ti 3 C 2 H 2 > Ti 3 C 2 O 2 > Ti 3 C 2 F 2 > Ti 3 C 2 S 2 > Ti 3 C 2 Cl 2 , depending on the varying charge density, charge transfer and adsorption energy. [46][47][48] Of all the MXenes Ti 2 CO 2 can be delaminated to the thinnest layers, and can be modified with a variety of functional groups, including F, OH and O, to enhance its selectivity towards NH 3 . [49][50][51] First principles simulation was used to examine the potential of monolayer Ti 2 CO 2 as a gas sensor by Yu et al It was observed that from all variant gases (NH 3 , N 2 , H 2 , O 2 , CH 4 , CO x and NO 2 ) only NH 3 is chemisorbed on monolayered Ti 2 CO 2 , with the observed charge transfer value 0.174.…”
Section: Pristine and Intercalated Mxenesmentioning
confidence: 99%